2015
DOI: 10.1080/0376835x.2015.1044078
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing adoption of genetically modified crops in Africa

Abstract: The debate around genetically modified (GM) crops in Africa continues to grow especially among policy-makers, food manufacturers, farmer organisation and consumer advocacy groups and the general public. While other regions have taken a firm position on biotech crops, Africa remains largely ambivalent, with wide variation in GM policy across countries. The central objective of this paper is to analyse the factors that influence the adoption of GM crops in Africa. First we evaluate the current status of GM crop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…In South Asia, for instance, Bhutan adopted a restrictive GMO-free strategy banning any introduction, release, or research of GMOs while India established federal and state agencies to regulate already commercialized GM crops [67]. In sub-Saharan Africa, South Africa among few others is a frontrunner of GM crop adoption and enacted GMO laws in 2000 while Angola prohibits GMOs with no enacted GMO laws [66,68]. Mabaya et al (2015) identified some key factors affecting GM crop policies in Africa [68], which might be applicable to South Asia.…”
Section: Caveats Of Developing Transgenic Pro-vitamin a Enhanced Cropmentioning
confidence: 99%
See 3 more Smart Citations
“…In South Asia, for instance, Bhutan adopted a restrictive GMO-free strategy banning any introduction, release, or research of GMOs while India established federal and state agencies to regulate already commercialized GM crops [67]. In sub-Saharan Africa, South Africa among few others is a frontrunner of GM crop adoption and enacted GMO laws in 2000 while Angola prohibits GMOs with no enacted GMO laws [66,68]. Mabaya et al (2015) identified some key factors affecting GM crop policies in Africa [68], which might be applicable to South Asia.…”
Section: Caveats Of Developing Transgenic Pro-vitamin a Enhanced Cropmentioning
confidence: 99%
“…In sub-Saharan Africa, South Africa among few others is a frontrunner of GM crop adoption and enacted GMO laws in 2000 while Angola prohibits GMOs with no enacted GMO laws [66,68]. Mabaya et al (2015) identified some key factors affecting GM crop policies in Africa [68], which might be applicable to South Asia. First, positions of line ministries are important; the ministry of agriculture tends to favor GM crops whereas the ministry of environment tends to view them as potential threats.…”
Section: Caveats Of Developing Transgenic Pro-vitamin a Enhanced Cropmentioning
confidence: 99%
See 2 more Smart Citations
“…Like the academic debate on GM crops and the poor, the public controversy around GM crops in Europe not only concerns domestic use but frequently extends to their role in the sustainable development of agriculture in the Global South [25][26][27]. Many have argued that the divergent positions of the US and EU have contributed to the current low adoption rates of GM in Africa [28][29][30], with only South Africa, Burkina Faso and Sudan having commercial plantations of GM crops [16].…”
Section: Introductionmentioning
confidence: 99%